1989
DOI: 10.1073/pnas.86.18.7186
|View full text |Cite
|
Sign up to set email alerts
|

Loss of distinct regions on the short arm of chromosome 17 associated with tumorigenesis of human astrocytomas.

Abstract: Astrocytomas, including glioblastoma multiforme, represent the most frequent and deadly primary neoplasms of the human nervous system. Despite a number of previous cytogenetic and oncogene studies primarily focusing on malignant astrocytomas, the primary mechanism of tumor initiation has remained obscure. The loss or inactivation of "tumor suppressor" genes are thought to play a fundamental role in the development of many human cancers. Thus, we have analyzed astrocytomas of various histological malignancy gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…In contrast, loss of heterozygosity of loci on chromosome 10 was not seen in any of 13 benign constitutionally heterozygous tumours, whereas 14 out of 27 malignant tumours (52%) showed an abnormality. These results concur favourably with the data obtained in studies on nonBritish patient cohorts, and are consistent with the hypothesis that chromosome 17p loss may represent an event in the development of benign glial tumours, while loss of chromosome 10 alleles is associated with a transition to a malignant phenotype (James et al, 1988;James et al, 1989;El-Azouzi et al, 1989;and Fujimoto et al, 1989).…”
Section: Resultssupporting
confidence: 89%
“…In contrast, loss of heterozygosity of loci on chromosome 10 was not seen in any of 13 benign constitutionally heterozygous tumours, whereas 14 out of 27 malignant tumours (52%) showed an abnormality. These results concur favourably with the data obtained in studies on nonBritish patient cohorts, and are consistent with the hypothesis that chromosome 17p loss may represent an event in the development of benign glial tumours, while loss of chromosome 10 alleles is associated with a transition to a malignant phenotype (James et al, 1988;James et al, 1989;El-Azouzi et al, 1989;and Fujimoto et al, 1989).…”
Section: Resultssupporting
confidence: 89%
“…In astrocytomas this study has found that the nuclear Vogelstein et al, 1989;Iggo et al, 1990;Harris et al, 1990;Menon et al, 1990 (James et al, 1989;El-Azouzi et al, 1989) (James et al, 1988 (Masuda et al, 1987;Mulligan et al, 1990;Malkin et al, 1990). Only precursors giving rise to high grade astrocytomas may be affected by transforming p53 mutations leading to overexpression of the p53 mutants, similar to that reported in carcinoma of the breast and lung (Cattoretti et al, 1988;Iggo et al, 1990).…”
Section: Discussionsupporting
confidence: 69%
“…However, the onset of the malignant process is highly variable, and prognostic predictions cannot be made in individual patients. In both low and high grade astrocytomas loss of heterozygosity for alleles on chromosome 17p has recently been found, suggesting that during early stages of tumorigenesis mutation and acquisition of homozygosity has occurred in a recessive oncogene on that chromosome (James et al, 1989;El-Azouzi et al, 1989). Also, several high grade astrocytomas have been found to contain point mutations in gene p53, which is localised on chromosome 17p .…”
mentioning
confidence: 99%
“…Molecular genetic studies have demonstrated that both inactivation of tumor-suppressor genes as well as oncogene amplification are important in the malignant progression of human gliomas (Holland, 2001). In particular, critical genes coding for growth factors, and their receptors (Ekstrand et al, 1991;Takahashi et al, 1992;Wong et al, 1992;Guha et al, 1995), as well as genes involved in cell cycle regulation (El-Azouzi et al, 1989;Jen et al, 1994;Henson et al, 1994;Reifenberger et al, 1994) are differentially overexpressed or altered in glial tumors. The progression to glioblastoma multiforme (GBM) involves losses of expression of tumor-suppressor proteins on chromosome 10 in a subset of tumors (Mollenhauer et al, 1997;Sano et al, 1999).…”
Section: Introductionmentioning
confidence: 99%